FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN FUNGSI KOGNITIF PADA LANSIA - Syahrum, Dahlia, Deharnita (Menara Ilmu : Jurnal Penelitian dan Kajian Ilmiah, 2016)
Cognitive function will further decrease with age. Cognitive function in the elderly is influenced by several factors such as age, sex, education, descent, and comorbidities. Based on the preliminary study, it was found mostly elderly impaired cognitive function. The purpose of this study was to determine the factors associated with the function.This study is a descriptive analyst with cross sectional study conducted in January-June 2016, with the entire population of elderly who live in PSTW Sabai Nan Aluih. Sampling using sampling total of 60 elderly. Data were collected by interview using a questionnaire Mini Mental State Examination (MMSE), which is then processed and analyzed using univariate and bivariate using Chi-Square.The results were obtained less than a majority (45%) of respondents have a level of normal cognitive function, more than the majority (51.7%) of respondents are in the category of elderly parents are aged 70-90 years, more than a majority (63.3%) respondents gender boys -Eighteen, less than a majority (45%) of respondents had a recent education at the elementary school level / equivalent. From the test results obtained statistically significant relationship between age, education and gender on cognitive function in the elderly PSTW Sabai Nan Aluih Sicincin 2016.To maintain / improve the cognitive function of elderly, caregivers or health workers in PSTW Sabai Nan Aluih Sicincin need to do activities that can stimulate cognitive function of elderly besides gymnastics activities, such as the distribution of interests and talents, Reminiscence therapy, brain gymnastics etc. Keywords: Cognitive Function elderly, factors related